Avidity characterization of genetically engineered T-cells with novel and established approaches. (December 2016) - Hillerdal, Victoria; Boura, Vanessa; Björkelund, Hanna; Andersson, Karl; Essand, Magnus
Abstract Background Adoptive transfer of genetically engineered autologous T-cells is becoming a successful therapy for cancer. The avidity of the engineered T-cells is of crucial importance for therapy success. We have in the past cloned a T-cell receptor (TCR) that recognizes an HLA-A2 (MHC class I)-restricted peptide from the prostate and breast cancer- associated antigen TARP. Herein we perform a side-by-side comparison of the TARP-specific TCR (TARP-TCR) with a newly cloned TCR specific for an HLA-A2-restricted peptide from the cytomegalovirus (CMV) pp65 antigen. Results Both CD8+ T-cells and CD4+ T-cells transduced with the HLA-A2-restricted TARP-TCR could readily be detected by multimer analysis, indicating that the binding is rather strong, since binding occured also without the CD8 co-receptor of HLA-A2. Not surprisingly, the TARP-TCR, which is directed against a self-antigen, had weaker binding to the HLA-A2/peptide complex than the CMV pp65-specific TCR (pp65-TCR), which is directed against a viral epitope. Higher peptide concentrations were needed to achieve efficient cytokine release and killing of target cells when the TARP-TCR was used. We further introduce the LigandTracer technology to study cell-cell interactions in real time by evaluating the interaction between TCR-engineered T-cells and peptide-pulsed cancer cells. We were able to successfully detect TCR-engineered T-cell binding kinetics to the target cells. We also used the xCELLigence technology to analyzed cell growth of target cells to assess the killing potency of the TCR-engineered T-cells. T-cells transduced with the pp65 - TCR exhibited more pronounced cytotoxicity, being able to kill their targets at both lower effector to target ratios and lower peptide concentrations. Conclusion The combination of binding assay with functional assays yields data suggesting that TARP-TCR-engineered T-cells bind to their target, but need more antigen stimulation compared to the pp65-TCR to achieve full effector response. Nonetheless, we believe that the TARP-TCR is an attractive candidate for immunotherapy development for prostate and/or breast cancer.